2020
DOI: 10.2217/pgs-2020-0021
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in Non-Small-Cell Lung Cancer: from Targeted Molecules to Resistance Patterns

Abstract: Immunotherapies are now considered as a pillar of non-small-cell lung cancer treatment. The main targets of immune-checkpoint inhibitors (ICI) are programmed cell death 1/programmed cell death ligand 1 and cytotoxic T-lymphocyte antigen 4, aiming at restoring antitumor immunity. Despite durable responses observed in some patients, all patients do not benefit from the treatment and almost all responders ultimately relapse after some time. In this review, we discuss the biomarkers that could be used to predict r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…[ 4 , 5 ] The reason is that the existing immune escape theory and its clinical application focus on a single immune checkpoint corresponding to T cells in the adaptive immune system, and it is difficult to cope with the extensive heterogeneity and complex carcinogenic mechanism of NSCLC. [ 6 ] Therefore, new immune escape theories and immunotherapy methods need to be explored and applied urgently.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 , 5 ] The reason is that the existing immune escape theory and its clinical application focus on a single immune checkpoint corresponding to T cells in the adaptive immune system, and it is difficult to cope with the extensive heterogeneity and complex carcinogenic mechanism of NSCLC. [ 6 ] Therefore, new immune escape theories and immunotherapy methods need to be explored and applied urgently.…”
Section: Introductionmentioning
confidence: 99%
“…Newer advanced technologies can be used to explore and evaluate the tumor microenvironment and the complexities of tumor and immune system interactions, going beyond the assessment of single analytes such as PD-L1. Recent studies have suggested that Tumor Mutational Burden (TMB), Microsatellite Instability and Mismatch Repair Deficiency, assessment of the Tumor Immune Microenvironment (TME) by T-cell tumor infiltration level evaluations, and gene expression profiles (GEPs) can correlate with the clinical response to immunotherapy [ 8 , 9 , 10 ]. Recent data have also suggested that immune-related gene signatures may predict the clinical response to immunotherapy.…”
Section: Introductionmentioning
confidence: 99%